Electrical measurement of tree root absorbing surfaces by the earth impedance method: 2. Verification based on allometric relationships and root severing experiments - Cermák, Jan; Ulrich, Radek; Stanek, Zdenek; Koller, Jan; Aubrecht, Ludek (Tree physiology, 2006)
We validated, by means of allometric relationships and root severing experiments, the modified earth impedance method developed for measuring absorbing root surfaces. For the allometric studies, a series of 350 small and large trees of six broadleaf and coniferous species in several experimental sites was examined. We found a good linear ln-ln fit between absorbing root surface area and basal area (or stem cross-sectional area at the root collar in seedlings) over a range of stem diameters from 0.5-55 cm. The absorbing root surface area also changed consistently with crown projected area and the root-accessed area (territory) of the tree. At the whole-tree level, absorbing root surface area reached about 70 times that of basal area and 40% of crown projected area, or roughly 1/3 of the root-accessed area in Norway spruce (in this species, the ratio was relatively larger in small trees and smaller in large trees). The absorbing root surfaces of mechanically severed parts of Norway spruce root systems changed in about the same proportions as the geometrically determined parts of the severed root systems. These results are promising and support field applications of the method in biological and ecological studies.
Keywords: borovice; Trees; Quercus; Olea; buk (rod); Absorption; půda; Pinus; Soil; smrk; elektrická vodivost; stromy; Acer; absorpce; Fagus; Picea; dub (rod); Plant Roots; kořeny rostlin; Electric Conductivity